Marlene Dietrich : Portraits 1926-1960 - Sembach, Klaus-Jürgen; von Sternberg, Josef (Munich : Schirmer/Mosel, 1984)
Alexander, Kenneth ; Avedon, Richard ; Beaton, Cecil ; Blumenfeld, Erwin ; Boulton, Davis ; Bruehl, Anton ; von Bukovich, Mario ; Chidnoff, Irving ; Croner, Harry ; Eisenstaedt, Alfred ; English, Don ; Engstead, John ; Estabrook, Ed ; Gragnon, François ; Greene, Milton H. ; von Gudenberg, W. ; Horst, Horst P. ; Hoyningen-Huene, George ; Hurrell, George ; Jones, Ray ; List, Herbert ; Meisert, Harald ; Muray, Nikolas ; d'Ora ; Parkinson, Norman ; Penn, Irving ; Reed, Ted ; Richee, Eugene R. ; etc.
boek